Evidence-based social work practice with families : a lifespan approach - Corcoran, Jacqueline (Springer series on social work (Unnumbered), 2000)
Empirically-informed practice is increasingly important as managed health care environments demand accountability in mental health and health care services. In this comprehensive text, Dr. Corcoran makes implementing evidence-based clinical practice easy. She reviews the most common problem areas social workers encounter. Each chapter assesses the family treatment outcome literature, addresses different theoretical orientations, summarizes the most current clinical research studies, and provides information on standardized, self-report instruments and their validity. Topics include: child phys.